Implementasi Pembimbingan Berkelanjutan Dapat Meningkatkan Kompetensi Guru dalam Menyusun Perangkat Pembelajaran Khususnya RPP pada MTs Yapit Malakaji Kabupaten Gowa - Aminah, St (UNIVERSITAS NEGERI MAKASSAR, 2019)
This school action research uses a continuous mentoring model. The purpose of this model is for teachers to improve their competence in developing learning tools. More specifically this PTS is to obtain an overview of the teacher's understanding in preparing a complete RPP and implementing it in class.There are four stages that become the focus of problem solving to improve teacher competence in preparing a complete RPP, namely planning, implementation, observation, and reflection.Based on data analysis in cycle I and II, continuous mentoring can improve teacher competence in preparing lesson plans. This can be proven from the results of observations which show that there is a significant increase in teacher competency in preparing lesson plans from cycle to cycle. In Cycle I there were 8 teachers or 34.78% whose performance scores were in the high category while in Cycle II there were 19 teachers or 82.61%. This shows an increase of 47.83%.